Problems of Cryptocurrency Transactions: Foreign Experience and Development Prospects in Ukraine - Подцерковний, Олег Петрович; Подцерковний, О. П.; Подцерковный, Олег Петрович; Podtserkovnyi, Oleh P.; Podtserkovnyi, Oleg; Резнік, Надія Петрівна; Резнік, Н. П.; Резник, Надежда Петровна; Reznik, Nadiia P.; Згама, Антоніна Олександрівна; Згама, А. О.; Згама, Антонина Александровна; et al. (Springer Nature, 2021)
The article is devoted to the research of the problem of legal regime of cryptocurrency under the legislation of Ukraine and foreign countries, which is due to the lack of proper legal regulation of cryptocurrency circulation in Ukraine. The legal nature of cryptocurrency is analyzed and suggested ways to overcome the decentralization of the last. The subject of this paper is the representation of the cryptocurrency transactions in the modern socioeconomic conditions. The results of the article are aimed at developing theoretical provisions for determining the legal regime of cryptocurrency and related categories. In the course of writing the article, a step-by-step model of consolidating virtual assets in the legislation of Ukraine was formed. The following methods were used throughout the researching process: the dialectical method, the method of systematic-structural analysis, comparative method, forma1-1ega1 method, as well as other methods and scientific approaches. The results of this research are of crucial importance for practice and theory as it provides deep understanding of the nature of cryptocurrency. The article provides the readers with the essence of virtual assets, allowing scholars and practitioners to understand the particularities of cryptocurrency transactions. The importance of this research’s results increases taking into account it should be used as a legal guide for the participants of the commercial relations, being forced to adapt their economic activity to the modem conditions.

Стаття присвячена дослідженню проблеми правового режиму криптовалюти за законодавством України та зарубіжних країн, що пов’язано з відсутністю належного правового регулювання обігу криптовалют в Україні. Проаналізовано правову природу криптовалюти та запропоновано шляхи подолання децентралізації останньої. Предметом даної роботи є представлення криптовалютних операцій в сучасних соціально-економічних умовах. Результати статті спрямовані на розробку теоретичних положень щодо визначення правового режиму криптовалюти та суміжних категорій. У ході написання статті була сформована покрокова модель консолідації віртуальних активів у законодавстві України. У процесі дослідження використовувалися такі методи: діалектичний метод, метод систематико-структурного аналізу, порівняльний метод, метод forma1-1ega1, а також інші методи та наукові підходи. Результати цього дослідження мають вирішальне значення для практики та теорії, оскільки дають глибоке розуміння природи криптовалюти. Стаття дає читачам суть віртуальних активів, дозволяючи науковцям і практикам зрозуміти особливості операцій з криптовалютою. Важливість результатів цього дослідження зростає, оскільки його необхідно використовувати як правовий посібник для учасників комерційних відносин, які змушені адаптувати свою господарську діяльність до сучасних умов.
Podtserkovnyi O. Problems of Cryptocurrency Transactions: Foreign Experience and Development Prospects in Ukraine / O. Podtserkovny, N. Reznik, A. Zghama, S. Tsurkanu, I. Kovalevych // Lecture Notes in Networks and Systems : International Conference on Business and Technology. - LNNS, volume 194. - Springer Nature, 2021. - P. 847 – 857.
Keywords: cryptocurrency; virtual asset; legal regime; economic activity; state regulation; taxation; криптовалюта; віртуальний актив; правовий режим; господарська діяльність; державне регулювання; оподаткування; Research Subject Categories::LAW/JURISPRUDENCE